Synthesis and characterization of substituted dithiocarbamates ligands and complexes as a source of metal (Pb, Ni & Co) sulphide nanoparticles - Thangwane, Selaelo Christabel (Vaal University of Technology, 2017)
Lead, nickel and cobalt dithiocarbamates complexes were synthesized using methanol and water as solvents. All complexes were refluxed at 60 °C, cooled at room temperature, washed with methanol to remove the impurities and dried under the fume hood. A combination of Fourier transformer infrared (FTIR), elemental analysis (EA) and thermogravimetric analysis (TGA) were used to characterize these complexes. There was shifting of bands from low to high frequencies of the dithiocarbamates complexes compared to benzimidazole derivatives. The absence of the N-H band and the presence of new C=S bands confirmed that the complexes can be used in the preparation of metal sulphide nanoparticles. Elemental analysis showed that there was a percentage mismatch for the complexes I, III, IV and V. Complexes II and VI calculated percentages were within the limits with the found percentages except for sulphur which was low. The TGA curves decomposed to form a mixture of metal and metal sulphides for complex I, II, III and IV except for complex VI which gave metal sulphide only. All benzimidazole complexes decomposed at higher temperatures and were considered as stable complexes. Lead sulphide (PbS) is an important group IV-VI metal chalcogenide semiconductor. It has a direct narrow band gap of 0.41 eV at 300K and a large excitonic Bohr radius of 18 nm. Lead sulphide absorption band can be tuned to anywhere between near IR to UV (0.4μm) covering the entire visible spectrum, while achieving the quantum confinement region. The synthesis of lead sulphide nanoparticles was conducted by varying the effect of the reaction conditions such as the type of capping agents and temperature. Lead dithiocarbamate complex derived from benzimidazole, [Pb(S2N2C8H5)2] was thermolysed in hexadecylamine (HDA) and trioctylphosphine oxide (TOPO) at different reaction temperatures (140, 160 and 180 °C) to produce HDA and TOPO capped PbS nanoparticles. The nanoparticles were characterized using X-ray diffraction (XRD) for structural analysis, transmission electron microscopy (TEM) for shape and size, Ultraviolet visible (UV/Vis) and Photoluminescence (PL) spectroscopy for optical properties. An increase in temperature gave a decrease in the sizes of the nanoparticles when using the HDA capped lead benzimidazole dithiocarbamate complex. The observed morphology was cubes. TOPO capped lead benzimidazole dithiocarbamate complex gave no specific trend when temperature was varied. A cross-like layer with quasi spherical particles on top was observed at 160 °C. At 180 °C, the cross-like layer decomposed into rods- like materials with quasi spherical particles on top for TOPO capped PbS nanoparticles. For lead 2-methylbenzimidazole [Pb(S2N2C9H7)2] dithiocarbamate complex, TOPO capped PbS produced agglomerated cubic morphology at low temperature but as the temperature was increased agglomerated cylindrical shapes were observed. HDA capped PbS produced polydispersed nanocubes which were increasing in size when the temperature was increased. Nanoparticles displayed a blue shift in band edges with good photoluminescence behaviour which was red shifted from their respective band edges all temperatures and capping agents. XRD confirmed the crystal structure of cubic phase (galena) of PbS at all temperatures except for HDA capped PbS nanoparticles at 140 °C from lead benzimidazole dithiocarbamate complex which confirmed the crystal structure of face-centred cubic phase of PbS nanoparticles. Nickel sulphide has much more complicated phase diagram than cobalt sulfides and iron sulfides. Their chemical composition has many crystalline phases such as α-NiS, β=NiS, NiS2, Ni3S2, Ni3S4, Ni7S6 and Ni9S8. Ni3S2 phase has shown potential as a low-cost counter electrode material in dye sensitised solar cells, while the α-NiS phase has been applied as a cathode Material in lithium-ion batteries. The synthesis of nickel sulphide nanoparticles was done by varying the effect of the reaction conditions such concentration and temperature. Nickel benzimidazole dithiocarbamate [Ni(S2N2C8H5)2] and nickel 2-methylbenzimidazole [Ni (S2N2C9H7)2] dithiocarbamates complexes were thermolysed in hexadecylamine (HDA) at different reaction temperatures (140, 160 and 180 °C) and precursor concentrations (0.30, 0.35 and 0.40 g) to produce HDA capped NiS nanoparticles. It was observed that increasing both temperature and precursor concentration increased the size of the nanoparticles. Anisotropic particles were observed for both complexes when varying precursor concentration and temperature. Nickel benzimidazole dithiocarbamate complex produced stable shapes (spheres and cubes) of nickel sulphide nanoparticles. Nickel 2-methylbenzimidazole dithiocarbamate complex produced a mixture of spheres, cubes, triangles and rods nickel sulphide nanoparticles at all concentrations. But when varying temperature, it only produced that mixture at 160 °C. The optical measurements supported the presence of smaller particles at all temperatures and concentrations. XRD showed the presence of C7OS8 and pure nickel as impurities. However, the crystal structure of cubic Ni3S4 was observed at low temperatures and an introduction of monoclinic NixS6 at high temperature (180 °C) when varying temperature for both complexes. When varying concentration using nickel benzimidazole dithiocarbamate complex, XRD showed the presence of NiSO4.6H2O impurities at high temperatures. At 160 °C a mixture of hexagonal NiS and cubic Ni3S4 was observed. At low temperatures only nickel as a metal was found as an impurity and the crystal structure of cubic Ni3S4 was observed. When nickel 2-methylbenzimidazole complex was used, C7OS8 and pure nickel were found as impurities but the crystal structure of cubic Ni3S4 was observed. Cobalt sulphide (CoS) belongs to the family of group II-IV compounds with considerable potential for application in electronic devices. They have a complex phase diagram and their chemical composition have many phases such as Co4S3, Co9S8, CoS, Co1-xS, Co3S4, Co2S3 and CoS2. The synthesis of cobalt sulphide nanoparticles was conducted by varying the effect of temperature on size and shape of the nanoparticles. Nickel benzimidazole dithiocarbamate, [Ni(S2N2C8H5)2] and nickel 2-methylbenzimidazole [Ni(S2N2C9H7)2] complexes were thermolysed in hexadecylamine (HDA) at different reaction temperatures (140, 160 and 180 °C) to produce HDA capped CoS nanoparticles. Cobalt benzimidazole dithiocarbamate complex produced close to spherical shapes nanoparticles at all temperatures. The images showed that as temperature was increased, the size of the particles decreased. All the main reflection peaks were indexed to face-centred cubic Co3S4 and there were some impurities of C7OS8 at all temperatures. The optical measurements supported the presence of smaller particles at all temperatures. Cobalt 2-methylbenzimidazole dithiocarbamate complex produced big and undefined morphology. The optical properties were also featureless and XRD only showed impurities of C7OS8. The impurity is thought to be generated from a side reaction between benzimidazole and carbon disulphide to give this persistent organic moiety.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Nickel (Ni) sulphide nanoparticles; Cobalt (Co) sulphide nanoparticles; Lead (Pb) sulphide nanoparticles; Metal sulphide nanoparticles; Dissertations, Academic -- South Africa.; Nanoparticles.